2014
DOI: 10.1200/jco.2013.52.5782
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Primary Androgen-Deprivation Therapy for Clinically Localized Prostate Cancer

Abstract: We found no mortality benefit from PADT compared with no PADT for most men with clinically localized prostate cancer who did not receive curative intent therapy. Men with higher-risk disease may derive a small clinical benefit from PADT. Our study provides the best available contemporary evidence on the lack of survival benefit from PADT for most men with clinically localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…Indeed, some studies hypothesize that the decreased overall survival in men treated with ADT is related to the higher rates of cardiovascular deaths in this population [38,39]; however, the mere presence of baseline comorbidities associated with the development of cardiovascular disease may not modify the risk attributable to ADT [40]. As such, it is important to consider the cardiovascular risk of ADT in patient populations for whom no cancer benefit of treatment has been documented; for example, in patients with low-risk localized PCa [32,41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies hypothesize that the decreased overall survival in men treated with ADT is related to the higher rates of cardiovascular deaths in this population [38,39]; however, the mere presence of baseline comorbidities associated with the development of cardiovascular disease may not modify the risk attributable to ADT [40]. As such, it is important to consider the cardiovascular risk of ADT in patient populations for whom no cancer benefit of treatment has been documented; for example, in patients with low-risk localized PCa [32,41].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who receive ADT may need injections every several months and are at an advanced stage of disease that requires more checkups. 6 Given that study outcomes were identified by using administrative data, individuals with more frequent visits may be more likely to be diagnosed with adverse events because of a greater number of physician encounters and more numerically likely to have an instance of the defined study outcome term appear in the medical record as a result of a greater number of records.…”
Section: 3mentioning
confidence: 99%
“…The effect of pADT on patients with LE <5 yr is less clear, and may be beneficial for some men with shorter LE (Supplementary Table 1). A study by Potosky et al [29] recently examined the effectiveness of pADT using a propensity score standardized analysis and relying on data from the HMO Cancer Research Network. In their study, pADT was associated with a lack of overall survival benefit.…”
Section: Discussionmentioning
confidence: 99%